Allegoresis : Reading Canonical Literature East and West - Zhang Longxi (Book collections on Project MUSE., 2005)
Zhang Longxi examines the rise and development of allegorical readings, discussing them from a broad perspective that bridges the east/west divide and looking at their social and political implications.